Moonshine markets : issues in unrecorded alcohol beverage production and consumption - Haworth, Alan; Simpson, Ronald (Series on alcohol in society., 2004)
Moonshine Markets, the sixth book in the ICAP Series on Alcohol in Society, explores consumption patterns of a type of alcohol that is generally, but not exclusively, illegal in most of the countries where it is consumed.